Childhood disability and its associated perinatal characteristics in Bao'an district of Shenzhen, China - Xue Zhong; Xiaoli Zhao; Zhuoya Liu; Yuqin Guo; Liya Ma (BMC, 2020)
Abstract Background Disability has become a public health issues in China and around the world. This study aimed to report prevalence of children with disability by gender, delivery mode, birth weight, gestational age, birth defect and impairment type in the past 15 years in Baoan District, Shenzhen. Methods Data of children with all types of disability from year 2004 to 2018 was obtained from the registry database of Baoan Disabled Persons Federation. Their perinatal information, including gender, delivery mode, birth weight, gestational age, birth defect were traced from Shenzhen Maternal and Child Health Management System and compared with the whole registered population live births information in this district. Data of children with disabilities were included to calculate the prevalence (%). Results An overall prevalence of children disability was 1.02% in Baoan district, Shenzhen, in the past 15 years. The overall as well as mental disability prevalence rose from the first 5 years period (2004 to 2008) to the second 5 years of 2009 to 2013, and then dropped to the lowest level in the third 5 year of 2014-2018. Mental disability and intelligent disability accounted for the highest proportion. More than 70% of all kinds of the disabilities except mental disability were detected before 1 year old, 87% of the mental and intelligent disabilities were found before 3 years old. The Percentages of male, premature, low birth weight infants and children with cesarean, birth defect in disable children were higher than in whole population live birth children. Conclusions The overall prevalence of disability declined in the district after specific policy engagement. Mental and intelligent disabilities were still the most common disability in the district. The age of 0-3 years was an important period for early childhood detection and intervention.